Chiral Self-Assembly of Porphyrins Induced by Chiral Carbon Dots - Liu, Xiaowei; Lu, Jiayi; Chen, Jingqi; Zhang, Mengtian; Chen, Yingying; Xing, Feifei; Feng, Lingyan (Frontiers in Chemistry, 2020)
Chirality plays a key role in many fields ranging from life to natural sciences. For a long time, chiral materials have been developed and used to interact with chiral environments. In recent years, fluorescent carbon dots (CDots) are a new class of carbon nanomaterials exhibit excellent optical properties, good biocompatibility, excellent water solubility and low cost. However, chirality transfer between semiconductor CDots and organics remains a challenge. Herein, a facile one-step hydrothermal method was used to synthesize chiral CDs from cysteine (cys). The obtained chiral CDots can act as chiral templates to induce porphyrins to form chiral supramolecular assemblies. The successful transmission of chiral information provides more options for the development of various chiral composite materials and the preservation of chiral information in the future.